How did Nunavummiut youth cope during the COVID-19 pandemic? A qualitative exploration of the resilience of Inuit youth leaders involved in the I-SPARX project. Issue 1 (31st December 2022) - Thomas, Alaina; Bohr, Yvonne; Hankey, Jeffrey; Oskalns, Megis; Barnhardt, Jenna; Singoorie, Chelsea
ABSTRACT: This study investigated how COVID-19 has affected the wellness of a group of Inuit youth leaders in Nunavut in the context of their involvement with an ongoing mental health research initiative, the Making I-SPARX Fly in Nunavut [ I-SPARX ] project. The study had three goals: (1) to understand how the pandemic has affected I-SPARX leaders' perceived involvement in the I-SPARX Project ; (2) to build knowledge around how the pandemic has impacted the daily life and wellbeing of youth in Nunavummiut communities; and (3) to acquire a culturally specific understanding of their coping mechanisms and resilience strategies through the lens of Inuit Qaujimajatuqangit (IQ). Nine Inuit youth were interviewed virtually about their participation in I-SPARX, their life during the pandemic, and their coping strategies. Their comments were analysed using inductive thematic analysis. Pandemic challenges, the utility of I-SPARX teachings and participation, and culturally and community-embedded pathways to resilience were discussed. The implications of COVID-19 on Inuit youth in remote communities are not fully understood. The current study illuminates their experiences of the pandemic to inform future research on ways in which Inuit youth might be supported in situations, such as a global pandemic, that restrict their traditional resilience-enhancing activities and create social isolation.